Statistical Treatment of 'Build-Own-Operate-Transfer+L2306 Schemes - Donaghue, Brian (Washington, D.C. : International Monetary Fund, 2002)
The paper argues that assets produced under build-own-operate-transfer (BOOT) schemes-under which public infrastructure assets are legally owned and operated for a defined period by the private corporation that constructs them, before being transferred to the government- should be treated in macroeconomic statistics as owned by the government from the outset. The paper considers three approaches to the treatment of the economic stocks and flows entailed in these arrangements. While the preferred approach conceptually is to impute the creation and extinguishment of financial assets and liabilities, this approach is not consistent with the System of National Accounts 1993, and therefore an operating lease approach to BOOT schemes is recommended.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet